Cocatalysts in Semiconductor‐based Photocatalytic CO2 Reduction: Achievements, Challenges, and Opportunities - Ran, Jingrun; Jaroniec, Mietek; Qiao, Shi‐Zhang (Advanced materials (Weinheim), 2018)
Ever‐increasing fossil‐fuel combustion along with massive CO2 emissions has aroused a global energy crisis and climate change. Photocatalytic CO2 reduction represents a promising strategy for clean, cost‐effective, and environmentally friendly conversion of CO2 into hydrocarbon fuels by utilizing solar energy. This strategy combines the reductive half‐reaction of CO2 conversion with an oxidative half reaction, e.g., H2O oxidation, to create a carbon‐neutral cycle, presenting a viable solution to global energy and environmental problems. There are three pivotal processes in photocatalytic CO2 conversion: (i) solar‐light absorption, (ii) charge separation/migration, and (iii) catalytic CO2 reduction and H2O oxidation. While significant progress is made in optimizing the first two processes, much less research is conducted toward enhancing the efficiency of the third step, which requires the presence of cocatalysts. In general, cocatalysts play four important roles: (i) boosting charge separation/transfer, (ii) improving the activity and selectivity of CO2 reduction, (iii) enhancing the stability of photocatalysts, and (iv) suppressing side or back reactions. Herein, for the first time, all the developed CO2‐reduction cocatalysts for semiconductor‐based photocatalytic CO2 conversion are summarized, and their functions and mechanisms are discussed. Finally, perspectives in this emerging area are provided. Active and stable CO2‐reduction cocatalysts can obviously enhance the efficiency, selectivity, and stability of semiconductor‐based photocatalytic CO2 reduction. All of the developed CO2‐reduction cocatalysts are summarized, and their functions and insightful mechanisms are discussed. This can pave new avenues to the exploration of novel highly active and selective cocatalysts, toward high‐performance solar fuel production.